The lotus shoes [large type] - Yang, Jane (Writer) (Thorndike Press, a part of Gale, a Cengage Company, 2025)
1800s China. Tightly bound feet, or "golden lilies," are the mark of an honorable woman, eclipsing beauty, a rich dowry and even bloodline in the marriage stakes. When Little Flower is sold as a maidservant to Linjing, a daughter of the prominent Fong family, she clings to the hope that one day her golden lilies will lead her out of slavery. Not only does Little Flower have bound feet, uncommon for a muizai, but she is extraordinarily gifted at embroidery, a skill associated with the highest class of a lady. Resentful of her talents, Linjing does everything in her power to thwart Little Flower's escape. But when scandal strikes the Fongs, both women are cast out to the Celibate Sisterhood, where Little Flower's artistic prowess catches the eye of a nobleman. His attention threatens not only her improved status, but her life, the Sisterhood punishes disobedience with death. And if Linjing finds out, will she sabotage Little Flower to reclaim her power, or will she protect her?